Dystonia gravidarum: The twists and turns during pregnancy - Abhishek Lenka; L K Prashanth (Annals of Movement Disorders, 2022)
Objectives: To highlight the clinical significance of de novo dystonia and its spontaneous resolution during pregnancy. Methods: Two patients were evaluated in a movement disorder clinic during their first trimester of pregnancy and followed up longitudinally. Results: Our first patient developed severe right torticollis and laterocollis during the sixth week of pregnancy. No etiology could be identified by a series of laboratory and imaging investigations for dystonia. The patient had near-complete resolution of cervical dystonia, without any therapeutic interventions. The second patient developed cervical dystonia and severe neck spasms during the eighth week of pregnancy, and no identifiable etiologies were found. Because of the extreme severity of dystonia, the patient had to undergo medical termination of pregnancy, after which the dystonia subsided. Discussion: The literature on de novo dystonia in pregnancy or “dystonia gravidarum” is limited. To date, only three such cases have been reported. Our report expands the literature on this rare phenomenon. The cases in our study highlight that new movement disorders during pregnancy may indicate aberrant dopamine receptor sensitivity in a hyperestrogenic environment and that they are often self-limiting.